2019
DOI: 10.1177/1042258719855965
|View full text |Cite
|
Sign up to set email alerts
|

Can One Stone Kill Two Birds? Political Relationship Building and Partner Acquisition in New Ventures

Abstract: We extend the resource dependence theory to argue for the opposing effects of political relationship building on new ventures’ abilities to obtain suppliers and buyers. By signaling endorsement and better access to resources, political connection enhances new ventures’ legitimacy and bargaining position. In supply chains featuring high contractual uncertainties, suppliers favor new ventures with higher certainty of payment but buyers can be deterred by new ventures more difficult to control. Hence, paradoxical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 51 publications
4
54
0
Order By: Relevance
“…This novel finding puts a caveat on the persistent implication from the extant literature that political affiliation is always associated with benefits. We reinforce Luo et al (2019) and Fisman et al (2012) arguments that political relationship building can exert contradictory effects on a new venture's performance. Moreover, our results demonstrate that while state ownership is conducive to firm performance, actual involvement by the government in firm governance may be detrimental (especially to revenues and TPF).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 74%
“…This novel finding puts a caveat on the persistent implication from the extant literature that political affiliation is always associated with benefits. We reinforce Luo et al (2019) and Fisman et al (2012) arguments that political relationship building can exert contradictory effects on a new venture's performance. Moreover, our results demonstrate that while state ownership is conducive to firm performance, actual involvement by the government in firm governance may be detrimental (especially to revenues and TPF).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 74%
“…In sum, China’s business environment is designed to channel scarce resources and privileges to the country’s ideologically favored, politically well-connected and oftentimes (partly) state-controlled corporations, many of which are listed at the country’s two stock exchanges in Shanghai and Shenzhen (Allen et al, 2005; Lardy, 2019). For entrepreneurs, strong, ambiguous government involvement in the economy can be expected to affect business success, and relations with suppliers and customers (Luo et al, 2020), and creates its own kind of opportunity for entrepreneurial behavior: In the extreme, Mou Qizhong of Nande Group, for which brokerage across industries via government infrastructure was a core competence—fraught with the danger of shifting opinion about what is politically acceptable—ended in jail when opinion shifted negative (Yang, 2007, Chapter. 7; case snippet in Yang, 2004).…”
mentioning
confidence: 99%
“…Some studies also highlight the dark side of developing government or political connections. For example, Su et al (2015) report that political networking in China weakens the positive linkage between entrepreneurial orientation and new venture performance while, in a recent paper, Luo et al (2020) reveal that political relationship building by Chinese new ventures can be an obstacle for customer acquisition because of concerns about certainty of payments and levels of control. have studied changes of entrepreneurs' political networking over time and found that more recent Chinese entrepreneurs built fewer political networks compared to entrepreneurs that started earlier, and that the focus of networking behavior has shifted from the establishment of ties with bureaucrats towards the management of such ties.…”
Section: Network Of Entrepreneursmentioning
confidence: 99%
“…Furthermore, in order to obtain entrepreneurial finance, it is highly important for new ventures to leverage their human and social capital, which are strongly considered by investors in East Asia (Wang, 2016;Zacharakis et al, 2007). Finally, while networking generally has been found to be very important for East Asian new ventures, recent studies indicate that political networking, which appears to have been particularly prevalent in China, may result in problematic outcomes, such as weakening the effectiveness of entrepreneurial orientation (Su et al, 2015) or becoming an obstacle for acquiring customers (Luo et al, 2020). These findings suggest that new venture entrepreneurs should subsequently focus on developing business ties in their networking activities.…”
Section: Practical Implicationsmentioning
confidence: 99%